STUDY OF THE BOKA (TREASURY) ADAT MARRIAGE OF THE CIA-CIA BUTON IN THE KALAULI HAMLET OF THE HILA-KAITETU DISTRICT, LEIHITU DISTRICT, CENTRAL MALUKU REGENCY - Wa Ima; Samuel M Wattimury (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
Background in research in the Kalauli Negeri Hila-Kaitetu sub-district Leihitu, Central Maluku Regency, there are various tribes including indigenous people, Butonese, Bugis, Makassarese, and other tribes. In social life, where the Buton tribes live side by side and foster good relations of kinship and kinship between the indigenous people and with other tribes. Customs that are still preserved and preserved by the Buton tribe in Maluku, especially in Central Maluku, precisely in the Kalauli Hamlet, in this case the marriage custom. Customary marriages are part of customary Buton tribes that use customary forms of marriage can have good aspects related to the system of norms, rules and values ​​that apply to Buton tribes in the Kalauli sub-village. So that after all the conditions of the customary marriage is maintained by the community supporters, especially the customary marriage of the Buton tribe. In the life of the Buton Cia-cia tribe in the Kalauli Negeri Hila-Kaitetu Hamlet, Leihitu District, Central Maluku Regency, in marriages there are various stages of marital custom that are still maintained, among others, namely the Boka custom (treasure money). which must be submitted from the prospective male bride to the bride-to-be. The purpose of this research is: to find out the traditional traditions of the Boka (Cone-Cia) Buton tribe marriage in Kalauli Negeri Hila-Kaitetu Hamlet, Leihitu District, Central Maluku Regency